Dukungan Orang Tua, Ekspektasi Karier dan Hubungannya dengan Motivasi Belajar Siswa di SMK Negeri 5 Malang - Laili Indah Sari Rohmawati; Henny Indreswari; Elia Flurentin; Laili Indah Sari Rohmawati; Henny Indreswari (Universitas Negeri Malang, 2023)
Abstract: This research examines the problems of lack of learning motivation experienced by students of SMK Negeri 5 Malang, as well as factors related to these problems. The purpose of this study is to determine the correlation between student learning motivation problems and parental support obtained by students and student expectations for future careers. This is important to research as a basis for providing services to increase student learning motivation. The type of research used is correlational descriptive research. The population in this study was class XI and XII at SMK Negeri 5 Malang. Sampling was performed using a Cluster Random Area. The data retrieval technique uses questionnaires and the data is analyzed using multiple linear analysis. The results of this study show that; (1) there is a correlation between parental support and student learning motivation; (2) there is a correlation between career expectations and learning motivation; (3) there is a correlation between parental support, career expectations and learning motivation. Results of this research can be used to provide services that can improve the provision of support from parents to students and also services that can increase students' expectations of future career. It is hoped that these services can increase student learning motivation. Abstrak: Penelitian ini mengkaji mengenai problematika kurangnya motivasi belajar yang dialami oleh siswa SMK Negeri 5 Malang, dan variabel lain yang berhubungan dengan permasalahan tersebut. Penelitian ini bertujuan untuk mengetahui gambaran korelasi antara dukungan orang tua dan ekspektasi karier dengan motivasi belajar siswa. Hal tersebut penting diteliti sebagai dasar pemberian layanan untuk meningkatkan motivasi belajar siswa. Jenis penelitian yang digunakan adalah penelitian deskriptif korelasional. Populasi pada penelitian ini adalah kelas XI dan XII di SMK Negeri 5 Malang. Pengambilan sampel dilakukan dengan menggunakan Cluster Random Area. Teknik pengambilan data menggunakan kuesioner dan data dianalisis menggunakan analisis linier berganda. Hasil penelitian ini menunjukan bahwa; (1) terdapat hubungan antara dukungan orang tua siswa dengan motivasi belajar siswa; (2) terdapat hubungan antara ekspektasi karier dengan motivasi belajar; (3) terdapat hubungan antara dukungan orang tua, ekspektasi karier dengan motivasi belajar. Hasil dari penelitian ini, dapat digunakan sebagai acuan dalam membuat program layanan bimbingan dan konseling. Diharapkan dari pemberian layanan tersebut, dapat meningkatkan dukungan orang tua, ekspektasi karier serta motivasi belajar siswa.